Teachers’ autodidacticism in the time of remote teaching - Buchcic, Elżbieta (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
The term “autodidacticism” should be interpreted as consciously guided learning with a possibility of using various forms of help from other people or institutions. On the other hand, remote learning is a distance learning with no direct contact between a student and a teacher. It enables education, different types of courses and trainings without having to leave the house. A computer and the Internet are enough to become participants on a virtual plane of any online course. E-learning brings many benefits, among others, a person who takes such course makes decisions about the speed of gaining the knowledge and about time of learning. This model is very flexible and removes territorial barriers. The offer is quite diverse - the most popular courses are obviously language courses that allow us to learn or improve foreign languages. Computer, assertiveness, negotiation, finance or teaching courses are also often chosen. We can find open as well as closed courses, dedicated for a particular group of people. These courses take place through the use of modern communication tools, including chats or information exchange in a form of an email. At the end of the course, the participant writes a paper or takes an online exam, receives a certificate confirming the completion of the course. Even though remote learning in the self-teaching process has its advantages and flaws, unfortunately, in the current situation there is no other way to organise professional development trainings. The diversity of available materials that the Internet offers allow us to learn on our own and develop in a particular field within autodidacticism.